GENERATION AND RECRYSTALLIZATION OF DIAMONDS IN THE UPPER MANTLE - Simakov S.K. (My University, 1988)
According to the meteoritic model of earth differentiation, liquid iron with carbon was generated in the initial period of differentiation. Thus, this event was close in time to the absolute age of the captive minerals of diamond and to the establishment of the ancient stable cratons and the beginning of outgassing of the mantle. The primary diamond nuclei were formed from melt containing liquid iron together with carbon in the early stages of planetary differentiation; subsequently, the diamonds probably experienced both solution and further growth from a fluid phase, with the extent of these processes depending on the concentration of nitrogen in the primary fluid.